The family visitor experience at heritage attractions: value creation within a service environment - Melvin, John D.S. (2016)
The world is becoming characterised by services. This evolution is transforming the way people consume services, with significant implications for both business and society (Ostrom, Bitner, Brown, Burkhard, Goul, Smith-Daniels, Demirkan and Rabinovich, 2010). The role of the consumer has also been transformed, with a much more active and integrated role envisaged (Grönroos, 2011; McColl-Kennedy, Vargo, Dagger, Sweeney and van Kasteren, 2012). The role of the organisation is now to facilitate consumer value creation through the design of the service system and appropriate provision of resources (Grönroos and Voima, 2013; Gummerus, 2013). Service-dominant logic (SDL), service logic (SL) and customer-dominant logic (CDL) have emerged, as marketing researchers attempt to better conceptualise the construct of value and how value is created. Recent definitions consider that value is a phenomenon relating to ‘value in use’ and ‘value in the experience’ (e.g. Heinonen and Strandvik, 2015; Helkkula, Kelleher and Pihlström, 2012b).